Переміщення в невагомості чотириланкового маятника з рухомою точкою кріплення - Запольський, Л. Л.; Адашевська, Ірина Юріївна; Шеліхова, Інеса Борисівна (Мелітопольський державний педагогічний університет ім. Богдана Хмельницького, 2019)
Досліджена геометрична модель розкриття в умовах невагомості чотириланкового маятника з рухомою точкою кріплення. Розгортання ланок на уявній площині відбувається завдяки впливу імпульсів піротехнічних реактивних двигунів на кінцеві точки ланок маятника. Задача полягає у вивченні поводження маятникових систем у невагомості. Механічну інтерпретацію тут можна пов’язати з космічною тематикою - коли трансформування елементів стержневої конструкції порівняти з коливанням багатоланкового маятника як системою змінюваної конфігурації. І взагалі, переважна кількість космічних апаратів за своєю механічною суттю є просторово розвиненими механічними системами змінюваної конфігурації для роботи в космосі в умовах близьких до невагомості. На актуальність обраної теми вказує необхідність дослідження можливої схеми процесу розкриття у невагомості стержневої конструкції маятникового типу з рухомою точкою кріплення. При цьому рушіями процесу слід обрати імпульсні піротехнічні реактивні двигуни, встановлені на кінцевих точках ланок стержневої конструкції. Вони набагато легші і дешевші порівняно, наприклад, з електродвигунами або пружинними пристроями. Опис динаміки одержаного інерційного розкриття виконано за допомогою рівняння Лагранжа другого роду. Результати можна використати при проектуванні систем розкриття орбітальних конструкцій в умовах невагомості, наприклад, секцій силових каркасів космічних інфраструктур.

The investigated geometrical model of the method of formation (opening) under conditions of weightlessness of the rod structure, the elements of which are connected like a four-link pendulum with a movable fixing point. Disclosure on the conditional plane is due to the influence of pulses of pyrotechnic jet engines on the end points of the structural elements. Description of the dynamics of the inertial opening of the structure is obtained using the Lagrange equation of the second kind. The results are intended for use in the design of systems for unfolding structures under conditions of weightlessness, for example, sections of power frames of space infrastructures. The investigated geometrical model of the method of formation (opening) under conditions of weightlessness of the rod structure, the elements of which are connected like a four-link pendulum with a movable fixing point. Disclosure on the conditional plane is due to the influence of pulses of pyrotechnic jet engines on the end points of the structural elements. Description of the dynamics of the inertial opening of the structure is obtained using the Lagrange equation of the second kind. The results are intended for use in the design of systems for unfolding structures under conditions of weightlessness, for example, sections of power frames of space infrastructures. The investigated geometrical model of the method of formation (opening) under conditions of weightlessness of the rod structure, the elements of which are connected like a four-link pendulum with a movable fixing point. Disclosure on the conditional plane is due to the influence of pulses of pyrotechnic jet engines on the end points of the structural elements. Description of the dynamics of the inertial opening of the structure is obtained using the Lagrange equation of the second kind. The results are intended for use in the design of systems for unfolding structures under conditions of weightlessness, for example, sections of power frames of space infrastructures. Disclosure on the conditional plane is due to the influence of pulses of pyrotechnic jet engines on the end points of the structural elements. Description of the dynamics of the inertial opening of the structure is obtained using the Lagrange equation of the second kind. The results are intended for use in the design of systems for unfolding structures under conditions of weightlessness, for example, sections of power frames of space infrastructures.
Movement in the weightlessness of a four-terminal pendulum with a mobile mounting point
Keywords: чотириланковий маятник; піротехнічні реактивні двигуни; процес розкриття в невагомості; рівняння Лагранжа другого роду; core construction; process of opening in space; four-link rod construction; Lagrange equation of the second kind